Developing A Philosophy of Scientific Advancement in Muhammadiyah Higher Education Institutions Based on Principles of AIK (Al-Islam and Kemuhammadiyahan) - Syamsul Anwar (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2021)
This article addresses critical ideas about constructing scientific philosophy within the Muhammadiyah and ‘Aisyiyah Higher Learning Institutions (PTMA) circles through the concept of integrating Al-Islam and Kemuhammadiyahan (Islam and Muhammadiyah Principles), abbreviated as AIK, into the process of developing knowledge and science. Thus, the author provides a broad definition of AIK and distinguishes it into three main aspects. In the next step, the author explains two reasons for developing scientific philosophy in PTMA, including internal reasons in Muhammadiyah and Islam and external ones related to the development of modern science. Consequently, two approaches can be applied to integrate AIK into scientific development through objective and subjective approaches. In definition, the objective approach is a way of dealing with the issues through analyzing and re-building the structure of science it including paradigm (ontology), theories and methods (epistemology), and applications (axiology). In contrast, the subjective approach is the enrichment of the scientist through considering science and religion as complementary instead of contradictory.